Bordel de bled, bordel au Bled : figures rurales de la prostitution au Maroc - Mustapha Qadéry (L’Année du Maghreb)
Because too many shortcuts are taken in the study of female prostitution in the Middle Atlas, this article, taking us back to colonial and postcolonial times, will attempt to portray the phenomena in a different manner. By examining several recollections, exploring individual stories, personal accounts, as well as historic information available on prostitution in this region, this article seeks to reconstruct unifying themes that allow rethinking its inscription in local social dynamics as well as studies on gender and sexuality.